Managing Micro Enterprises In Developing Economies : A Review Of Theoretical And Empirical Perspectives - brito, Robert de (JUSTBEST Journal of Sustainable Business and Management, 2025)
Micro enterprises play a vital role in the economic development of many developing countries, yet their managerial practices, resource constraints, and institutional environments remain insufficiently understood within the scholarly literature. This article reviews and synthesizes theoretical and empirical studies on the management of micro enterprises in developing economies over the past two decades. Drawing on multiple theoretical frameworks—including the Resource-Based View, dynamic capabilities, institutional theory, and social capital theory—this review maps the evolution of concepts used to explain how micro enterprises operate and survive in resource-limited and informal contexts. The methodology involves a structured qualitative review of peer-reviewed journal articles from major academic databases, focusing on thematic patterns across managerial practices, entrepreneurial behavior, innovation, gender dynamics, and financial access. The findings reveal fragmented research streams dominated by context-specific case studies, limited theorization, and methodological weaknesses that constrain the generalizability of insights across diverse developing regions. This article identifies four major research gaps related to theoretical integration, contextual diversity, digital transformation, and methodological rigor. A future research agenda is proposed to guide scholars toward more holistic, interdisciplinary, and context-sensitive investigations. By integrating insights across diverse studies, this review contributes a comprehensive understanding of micro enterprise management and provides a foundation for advancing knowledge and informing policy interventions in developing economies.